1996
DOI: 10.1046/j.1365-2567.1996.d01-635.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin stimulates production of interleukin‐8 in human umbilical vein endothelial cells

Abstract: SUMMARYInterleukin-8 (IL-8) is regarded as an important mediator of inflammation because of its potent and specific chemotactic activity on neutrophils. In the present investigation, human umbilical vein endothelial cells (HUVEC) stimulated with thrombin were found to produce IL-8, in a dose-and timedependent manner. After stimulation with 10 U/ml thrombin for 24 hr, the level of IL-8 in the conditioned medium was 14 ng/ml, or enough to elicit PMN chemotaxis in vitro. Northern blot analysis revealed that throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 25 publications
1
59
0
1
Order By: Relevance
“…As shown in Figure 1A, thrombin increased the IL-8 concentration in the culture media in a time and dose dependent manner, which is consistent with other previous reports (Ueno et al, 1996;Kaplanski et al, 1997;Johnson et al, 1998;Anrather et al, 1997). Therefore, we used thrombin as a stimulator for IL-8 synthesis from endothelial cells.…”
Section: Effect Of Thrombin On Il-8 Synthesis and Il-8 Mrna Expressiosupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 1A, thrombin increased the IL-8 concentration in the culture media in a time and dose dependent manner, which is consistent with other previous reports (Ueno et al, 1996;Kaplanski et al, 1997;Johnson et al, 1998;Anrather et al, 1997). Therefore, we used thrombin as a stimulator for IL-8 synthesis from endothelial cells.…”
Section: Effect Of Thrombin On Il-8 Synthesis and Il-8 Mrna Expressiosupporting
confidence: 92%
“…However, recent reports have revealed that IL-8 has also chemotactic eects on monocytes (Gerszten et al, 1999), T cells (Bacon et al, 1989), and aortic smooth muscle cells (Yue et al, 1993;, suggesting that IL-8 may have an important role in the progression of atherosclerosis. It has been reported that thrombin stimulates the production of IL-8 from endothelial cells (Ueno et al, 1996;Kaplanski et al, 1997;Johnson et al, 1998;Anrather et al, 1997). We also reported here that thrombin enhanced the production of IL-8 in AoEC at both the protein and mRNA levels (Figure 1), suggesting that thrombin may accelerate atherosclerosis by increasing the in¯ammatory responses including IL-8 production.…”
mentioning
confidence: 99%
“…The involvement of phosphatidylinositol turnover and PKC in stretch-induced signal transduction was previously demonstrated in experiments using the same stretch apparatus and the same types of cells, 44,45 and several stimuli were reported to upregulate gene expression of IL-8 and MCAF/MCP-1 through a PKCdependent pathway in ECs. [46][47][48] However, the correlation of these enzymes with the actin cytoskeleton remains to be clarified. The effect of mechanical forces on cell behavior involving gene expression has recently received increased attention, and both integrins and the actin cytoskeleton have been recognized to be strong candidates as mechanotransducers.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the thrombin receptor in a variety of cell types can elicit a range of cellular responses and expression of thrombin-responsive genes. Many of the gene products are precisely those that would be required for angiogenesis and tumor invasion, including IL-8 (Ueno et al, 1996), VEGF , bFGF (Cucina et al, 1999), PDGF (Shimizu et al, 2000), MMP-2 (Zucker et al, 1995), uPA (Yoshida et al, 1994) alpha IIb beta 3, alpha v beta 3, and alpha v beta 5 integrins (Wojtukiewicz et al, 1992;Senger et al, 1996;Even-Ram et al, 2001). This suggests that activation of the thrombin receptor may facilitate tumor invasion and metastasis through the induction of cell adhesion molecules, matrix-degrading proteases, and stimulating the secretion of angiogenic factors, thus contributing to the metastatic phenotype of melanoma.…”
Section: How Activation Of Par-1 Contributes To Melanoma Metastasismentioning
confidence: 99%